The Effect of Regional Independence and Dependence on Financial Sustainability in Government in South Sumatra Province - Dwi Rika Khairunisa; Yulia Saftiana; Rela Sari (Cita konsultindo, 2024)
This research is a research conducted with the aim of finding out how Regional Independence and Regional Dependence have an impact on Financial Sustainability. Goal Setting Theory emphasizes the importance of the relationship between goals and performance. This study is a quantitative research using a sample of 17 districts/cities based on data from the central E-PPID website of the Financial Audit Authority of the Republic of Indonesia, namely e-ppid.bpk.go.id. The results of this study show that regional independence and regional dependence have an effect on financial sustainability.